EXAMINATION OF THE COLLABORATIVE ROLE OF THE COURT AND THE POLICE IN THE PROTECTION OF SUSPECTS STATUTORY AND CONSTITUTIONAL RIGHTS - Nuhu , Abdullahi Liman; Zanwa, Ahmed Aliyu (LexScriptio A Journal of the Department of Jurisprudence and Public Law, 2025)
Suspect is someone who is accused or suspected of committing a crime. Every suspect is presumed to be innocent and also enjoy certain basic rights that are inalienable as well as undeniable. These rights are Constitutional and Statutory. All suspects enjoy right to life, dignity of human person, right to freedom of movement, and association, right to be informed of the offence, right to consult a legal practitioner and right to be granted bail or be taken to Court in good time. The Police has the Constitutional power to investigate crime while the Court adjudicate on all matters. In the course of investigation, there could be lawful arrest, search, detention, restriction of movement and prosecution. The process of the investigation should comply with the extant laws. Life of a suspect cannot be taken without court order. The pervasive problems are in the inhuman treatment, degradation, unlawful arrest, over detention, torture and physical abuse of suspect in custody which are clear violation of the suspect rights. This work adopted the doctrinal method of data collection which is basically a desk and library research. This work find out that Police Act 2020 and Administration of Criminal Justice Act 2015 and other laws, brought about robust reforms that gave hope and ensured that suspects rights are guided and protected through fairness, justice, speedy dispensation of cases and award of damages, disciplinary action, cum punitive measures for all erring Police officers The court served as a monitor to all violators of the right of a suspect